High and low temperature signalling and response. (20th November 2021) - De Smet, Ive; Quint, Marcel; van Zanten, Martijn
Abstract: Plants must deal with (sometimes extreme) temperatures ranging from intense cold (freezing) to severe heat. This necessitates adequate responses to tolerate temperature stress and/or maintain optimal performance. This special issue provides an update on the current knowledge of signalling and response mechanisms associated with both low and high temperatures in model species and relevant crops. A picture emerges that, although different temperature regimes are likely to involve dedicated signalling mechanisms, there is a degree of commonality and overlap in the responses and molecular networks involved.